Cervical ectopic pregnancy: a case report and review of the literature - Jukna, Povilas; Diržauskas, Marius (Lietuvos chirurgija, 2017)
Background Cervical pregnancy is a rare pathology with unclear etiology. This condition can be life-threatening and in certain situations be treated with total abdominal hysterectomy, although due to improving diagnostics, approach to cervical pregnancy’s management has been changing towards fertility preserving treatment. Case report 38 years old patient with vaginal bleeding and lower abdomen pain was admitted to Klaipėda Seamen‘s hospital. After thorough evaluation, clinical diagnosis of cervical pregnancy was confirmed. Different approaches were considered and total abdominal hysterectomy was determined as most suitable method. Surgery was successful and post-operative period was uneventful. Discussion Ultrasonography is the main diagnostic tool used to observe cervical ectopic pregnancy. Speculum and bimanual examination usually show prominent findings, assisting cervical pregnancy’s diagnose. Prior to improved diagnostic tools, total abdominal hysterectomy was the main approach treating cervical pregnancy. Now conservative management using methotrexate is considered as the first-line treatment and frequency of other fertility preserving procedures as suction curettage and tamponade or uterine artery embolization are increasing. Conclusion Data is limited because of cervical pregnancy’s rarity and every case of this condition has to be assessed separately. Desire to preserve fertility and patient’s condition must be taken to account before making decision on how cervical pregnancy will be managed.
Keywords: cervical pregnancy; ultrasonography; total hysterectomy